Deep Learned Quantization-Based Codec for 3D Airborne LiDAR Point Cloud Images - Tamilmathi, A. Christoper; Chithra, P. L. (Frontiers in Robotics and AI, 2021)
This paper introduces a novel deep learned quantization-based coding for 3D Airborne LiDAR (Light detection and ranging) point cloud (pcd) image (DLQCPCD). The raw pcd signals are sampled and transformed by applying the Nyquist signal sampling and Min-max signal transformation techniques, respectively for improving the efficiency of the training process. Then, the transformed signals are feed into the deep learned quantization module for compressing the data. To the best of our knowledge, this proposed DLQCPCD is the first deep learning-based model for 3D airborne LiDAR pcd compression. The functions of Mean Squared Error and Stochastic Gradient Descent optimization function enhance the quality of the decompressed image by 67.01 percent on average, compared to other functions. The model’s efficiency has been validated with established well-known compression techniques such as the 7-Zip, WinRAR, and tensor tucker decomposition algorithm on the three inconsistent airborne datasets. The experimental results show that the proposed model compresses every pcd image into constant 16-bits of data and decompresses the image with approximately 160 dB of PSNR value, 174.46 secs execution time with 0.6 secs execution speed per instruction, and proved that it outperforms the other existing algorithms regarding space and time.